Adipose derived mesenchymal stem cells express keratinocyte lineage markers in a co-culture model - Irfan-maqsood, M; Matin, M M; Heirani-Tabasi, A; Bahrami, M; Naderi-Meshkin, H; Mirahmadi, M; Hassanzadeh, H; Sanjar Moussavi, N; Raza-Shah, H; Raeesolmohaddeseen, M; Bidkhori, H; Bahrami, A R (Cellular and Molecular Biology, 2016)
Cutaneous wound healing is a complex type of biological event involving proliferation, differentiation, reprograming, trans/de-differentiation, recruitment, migration, and apoptosis of a number of cells (keratinocytes, fibroblasts, endothelial cells, nerve cells and stem cells) to regenerate a multi-layered tissue that is damaged by either internal or external factors. The exact regeneration mechanism of damaged skin is still unknown but the epithelial and other kinds of stem cells located in skin play crucial roles in the healing process. In this work, a co-culture model composed of adipose derived mesenchymal stem cells and keratinocytes was developed to understand the cellular differentiation behaviour in wound healing. Human mesenchymal stem cells were isolated from waste lipoaspirates. Keratinocytes were isolated from neonatal rats skin as well from human adult skin. Both types of cells were cultured and their culturing behaviour was observed microscopically under regular intervals of time. The identity of both cells was confirmed by flow cytometry and qRT-PCR. Cells were co-cultured under the proposed co-culturing model and the model was observed for 7, 14 and 21 days. The cellular behaviour was studied based on change in morphology, colonization, stratification, migration and expression of molecular markers. Expression of molecular markers was studied at transcriptional level and change in cellular morphology and migration capabilities was observed under the invert microscope regularly. Successfully isolated and characterized mesenchymal stem cells were found to express keratinocyte lineage markers i.e. K5, K10, K14, K18, K19 and Involucrin when co-cultured with keratinocytes after 14 and 21 days. Their expression was found to increase by increasing the time span of cell culturing. The keratinocyte colonies started to disappear after 10 days of culturing which might be due to stratification process initiated by possibly transdifferentiated stem cells. It can be concluded that mesenchymal stem cells can regenerate the damaged skin if transplanted to damaged area but for their successful differentiation and enhanced regeneration, they need a population of keratinocytes in situ which need further experiments for validation of co-culture model and its potential for being used in clinics.